THE ROLE OF PERCEIVED RISK AND ELECTRONIC WORD OF MOUTH (E-WOM) ON PURCHASING DECISIONS WITH TRUST AS A MEDIATOR - Firmansyah, Firby Rizqullah; Arif , Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to investigate the effects of perceived risk and electronic word-of-mouth (e-WOM) on purchase decision with trust as the mediating variable and Dust La Stella, a clothing brand, as the object. This study uses primary data obtained from questionnaires, which were distributed to 118 people who have purchased the product of the brand as the respondents. The results of the analysis using Partial Least Squares – Structural Equation Modeling demonstrate that perceived risk significantly and negatively influences the purchase decision, that e-WOM positively and significantly affects the purchase decision, and that trust positively and significantly influences the purchase decision. Furthermore, perceived risk negatively and significantly impacts trust, and trust does not mediate the impact of e-WOM and perceived risk on the purchase decision.